2018
DOI: 10.1089/gtmb.2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LncRNA-XIST Suppresses Proliferation and TGF-β1-Induced EMT in NSCLC Through the Notch-1 Pathway by Regulation of miR-137

Abstract: We identified a branch of the XIST/miR-137/Notch-1 pathway that regulates proliferation and TGF-β1-induced EMT in NSCLC, which could be involved in NSCLC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…The present findings clearly demonstrate that the expression of long non-coding RNA (lncRNA XIST) is upregulated in lung cancer cells, and it maybe involve in the cell proliferation and TGF-β1-mediated apoptosis [33]. And lncRNAXIST may have some functions by downregulating miRNA-144.…”
Section: Discussionmentioning
confidence: 52%
“…The present findings clearly demonstrate that the expression of long non-coding RNA (lncRNA XIST) is upregulated in lung cancer cells, and it maybe involve in the cell proliferation and TGF-β1-mediated apoptosis [33]. And lncRNAXIST may have some functions by downregulating miRNA-144.…”
Section: Discussionmentioning
confidence: 52%
“…In recent years, lncRNAs have been explored through functional analysis [32]. The present findings clearly demonstrate that the expression of long non-coding RNA (lncRNA XIST) is up-regulated in lung cancer cells, and it maybe involve in the cell proliferation and TGF-β1-mediated apoptosis [33]. And lncRNAXIST may have some functions by downregulating miRNA-144.…”
Section: Discussionmentioning
confidence: 54%
“…In Fig. 2 and Figure S2 a to d, we found that the expression levels of XIST, RELA, CD44, Slug, and ESA were remarkably decreased in the miR-7 mimic transiently transfected cells, especially in the case of XIST, which may regulate the stemness characteristics and tumorigenicity of some types of cancer cells, resulting in cancer progression [28][29][30][31][32][33]. To verify these claims, we attempted to identify whether XIST expression was regulated by miR-7/miR-92b.…”
Section: Discussionmentioning
confidence: 90%